Descrição de seis casos autóctones de leishmaniose visceral canina, diagnosticados em Pedregulho (São Paulo, Brasil) - De Abreu, Cássia Regina; Parpinelli, Ana Cláudia; De Lima, Romeika Reis; Gosuen Gonçalves Dias, Luis Gustavo [UNESP]; Freitas Pereira, Lucas De; Gonçalves Dias, Fernanda Gosuen (FapUNIFESP (SciELO), 2015)
Visceral leishmaniasis is an infectious disease of chronic, emerging and zoonotic nature that presents various degrees of severity. In Brazil, this illness is caused by Leishmania infantum (Leishmania chagasi), which is transmitted by the bite of the sand fly Lutzomyia longipalpis, and dogs are its main reservoir. Given the increasing spread of this disease across Brazil, the aim of this study was to report on six cases of canine visceral leishmaniasis, diagnosed in June 2013, in the city of Pedregulho, State of São Paulo, considered to be a non-endemic area and free of phlebotomine sand flies. The diagnosis was based on clinical signs of the patients and additional tests (serological and parasitological). It was concluded that the diagnosis of leishmaniasis is complex because the clinical signs are similar to other systemic diseases, thus justifying the importance of parasitological test of bone marrow, considered “gold standard”, in the confirmation of the disease. In addition, the area was not, until now, considered risk place, despite notification.
Description of six autochthonous cases of canine visceral leishmaniasis diagnosed in pedregulho (São paulo, brazil)
Keywords: Dermatopathy; Dog; Leishmania infantum; Protozoa; Zoonosis